Everyday Urban Practices in Africa: Disrupting Global Norms - Appelhans, Nadine (Routledge Studies in African Development, 2025)
This book disrupts the dominant underlying international norms informing urban development strategies across African cities. International policy frameworks have created a new universal agenda for developing cities. However, these frameworks have also imposed global paradigms and discourses that are often in conflict with local urbanisms. As we approach the deadline for achieving the Sustainable Development Goals, there is need for reflection and deliberation on a post-2030 agenda. The authors identify powerful assumptions, norms, and positionalities that obfuscate the efforts to achieve sustainable development in African cities, as well as along the North–South divide. They argue that a disruptive critique of these normative concepts, grounded in the lived African urban everyday, opens up opportunities to dismantle their assumed neutrality. Through disruption, the authors critically re-interpret the meanings of policy and the praxis of local urbanism, ultimately challenging the logic of universalising concepts underpinning implementation in the current international policy system, and asserting the need for contextualised urban policies. The book will be of interest to scholars and students of urban studies, development planning, urban governance, human settlements, development studies, urban geography, and African studies. It will also be useful for practitioners including town and regional/urban planners, urban policy consultants, and international development cooperation agencies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.